Patterns of Self-Medication Behavior for Oral Health Problems Among Adults Living in Riyadh, Saudi Arabia - Arwa Aldeeri; Haya Alzaid; Renad Alshunaiber; Shahad Meaigel; Naila A. Shaheen; Abdallah Adlan (MDPI AG, 2018)
Abstract: Self-medication is a widespread behavior worldwide. It is defined as the practice of self-diagnosis and drug prescription without proper professional consultation. Aim: To determine the prevalence and predictors of self-medication for oral health problems among adults living in Riyadh city. Methods: A cross-sectional study based on a structured close-ended questionnaire was distributed among adults visiting shopping malls in all different five regions of Riyadh. A two-stage sampling technique was used: cluster and simple random sampling. The questionnaire was composed of two main sections: demographic characteristics and questions assessing the behavior of self-medication. Results: The prevalence of self-medication was found to be 63.25%, with a higher prevalence among females than males. Gender and nationality were significantly associated with self-medication. Salt in hot water locally (52.57%) and acetaminophen (47.43%), a type of an analgesic, were, systemically, the most frequently used. Pharmacy shops were the main source of these medicaments (66.01%). Similarly, the advice for using them was mainly given by pharmacists (53.36%). Lack of time was claimed to be the main reason for practicing self-medication (54.55%) with abscess, toothache, and gingival bleeding being the main predictors. Conclusions: Self-medication was found to be a common practice among the population of Riyadh city.